2013
DOI: 10.1139/cjc-2012-0416
|View full text |Cite
|
Sign up to set email alerts
|

Computational study on the deamination reaction of adenine with OH/nH2O (n= 0, 1, 2, 3) and 3H2O

Abstract: Deamination of adenine is one of several forms of premutagenic lesions occurring in DNA. In the present study, mechanisms for the deamination reaction of adenine with OH−/nH2O (n = 0, 1, 2, 3) and 3H2O were investigated. HF/6-31G(d), B3LYP/6-31G(d), MP2/6-31G(d), and B3LYP/6-31+G(d) levels of theory were employed to search for and optimize all geometries. Energies were calculated at the G3MP2B3 and CBS-QB3 levels of theory. The effect of solvent (water) was computed using the polarizable continuum model (PCM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 35 publications
6
32
1
Order By: Relevance
“…The activation energy of the 1,3‐proton shift for the deamination of cytosine and guanine with OH − are lower with the respective values of 97 and 87 kJ mol −1 at G3MP2. The 1,3‐proton shift for deamination of adenine has an activation energy of 112 kJ mol −1 at G4MP2, which is comparable with this work on melamine to within 2 kJ mol −1 .…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…The activation energy of the 1,3‐proton shift for the deamination of cytosine and guanine with OH − are lower with the respective values of 97 and 87 kJ mol −1 at G3MP2. The 1,3‐proton shift for deamination of adenine has an activation energy of 112 kJ mol −1 at G4MP2, which is comparable with this work on melamine to within 2 kJ mol −1 .…”
Section: Resultssupporting
confidence: 81%
“…In comparison, the activation energy of the rate‐determining step ( TS1A ) for the deamination of cytosine and guanine with OH − are slightly lower with values of 148 and 155 kJ mol −1 at G3MP2, respectively. However, the activation energy of the rate‐determining step ( TS1A ) for the deamination of adenine is significantly higher, 189 kJ mol −1 at G4MP2 . The activation energy of TS1A is 185 kJ mol −1 at M06/6‐31G(d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous works of the 1,3-proton shift has shown that the barrier could drop significantly when the water molecule is involved, acting as a mediator [53][54][55][56][57][58][59][60][61][62][63][64][65]. Figure 5 shows the one-step nucleophilic addition mechanism for the monohydrated reaction between the methanol and CI.…”
Section: Potential Energy Surface For the Reaction Of Methanol With Cmentioning
confidence: 99%